Population structure analysis and construction of DNA fingerprinting in eggplant (Solanum melongena L.) based on whole-genome resequencing - Ruining Lai; Chuan Zhong; Jiechun Peng; Kongxiu Su; Duoduo Xiao; Bingying Zou; Meimei Shi; Jingjing Huang; Huarong Fang; Jinling He; Xinyuan Chen; Junwei Zhang; et al. (Genetic Resources and Crop Evolution, 2026)

Remote observation of the water clarity changes in Taihu Lake and the impacts of underwater tunnel construction based on Sentinel 2-MSI imagery - Xiangyu Xiang; Dian Wang; Jing Li; Guo Zheng (Journal of Oceanology and Limnology, 2026)

LncRNA SNHG14 drives alveolar inflammation in bronchopulmonary dysplasia via DNMT3a-mediated epigenetic silencing of miR-214-3p - Hui Hong; Xiaoxia Li; Jing Li; Yuhang Liu; Zhiqun Zhang (Inflammation Research, 2026)

Deep Immunophenotyping Unravels the Double Negative T cells and PD-1-Mediated Inflammatory Exhaustion in Ankylosing Spondylitis - Lu Bai; Jian Gao; Yunyun Xu; Yuexin Yu; Jing Liu; Mathias Hochgerner; Hejian Zou; Xingdong Chen; Feng Qian; Hongjun He; Jiucun Wang (Phenomics, 2026)
Ankylosing spondylitis (AS) is a chronic, immune-mediated inflammatory disorder primarily affecting the axial skeleton. It is characterized by bony fusion and syndesmophyte formation of the spine, leading to compromised mobility, reduced quality of life and increased mortality. However, the underlying immune dysregulation in AS remains poorly understood. We comprehensively profiled the peripheral immune landscape of 30 patients with active AS, all of whom were TNF-α blocker-naïve, capturing the immune profile during the active disease phase without biologic interference. Using advanced 11-color flow cytometry and FlowSOM clustering, 584 immunophenotypes were analyzed in AS and 30 age-and sex-matched healthy controls, with emphasis on both cellular composition and functional characteristics. AS patients displayed a distinctive functional “activated-exhausted” immune phenotype, dominated by CD4 + CD28 + CD38 + PD-1 + T cells and HLA-DR + CD38 + CD4 − CD8 − double-negative (DN) T cells. DN T cells were significantly enriched in HLA-B27-positive patients, suggesting potential as a biomarker. Network analysis revealed seven central immune subsets associated with active disease, while functional assessment demonstrated impaired CD95 + CD8 + T cell apoptosis and disrupted B-cell maturation. These findings provide a detailed functional immune map of biologic-naïve active AS, offering novel mechanistic insights and identifying candidate biomarkers for precision intervention.

Multi-mechanism modeling of gas-liquid hydraulic conductance - Qingyuan Zhu; Keliu Wu; Qiqi Liu; Fei Peng; Shengting Zhang; Jianlin Zhao; Jing Li; Japan Trivedi; Zhangxin Chen (Advances in Water Resources, 2026)

Sustainable tea production in western Sichuan: Defining optimal soil pH threshold to balance rhizosphere bacterial communities and flavor metabolites - Haojie Cao; Ning Ma; Siyu Wang; Ting Li; Zijun Zhou; Shirong Zhang; Yulin Pu; Yongxia Jia; Xiaojing Liu; Xiaoxun Xu; Guiyin Wang (Applied Soil Ecology, 2026)

Rhizosphere effect under drought stress: To explore its influence on microbial regulation of the soil carbon cycle - Yifan Wang; Wenjing Li; Hengfang Wang; Guanghui Lv (Applied Soil Ecology, 2025)

Differences in temporal patterns of bacterial community assembly between soybean rhizosphere and endosphere - Ting Jin; Shuanghui Wang; Yong Wu; Junyao Deng; Xuanjing Li; Yao Liu; Jianli Zhang; Wuxuan Li; Gehong Wei; Peng Shi (Applied Soil Ecology, 2025)

The interaction between mycorrhiza and phoD-harbouring bacteria influencing soil available phosphorus in Pinus massoniana plantations - Lifen Li; Yueming Liang; Qiang Li; Fujing Pan; Zhangqi Yang; Yanlan Wei; Yijing Li; Yanjun Chen; Hanlian Qin; Guangping Xu (Applied Soil Ecology, 2025)

Species interactions mediate arbuscular mycorrhizal fungi successional dynamics and glomalin-related soil protein accumulation in volcanic ecosystems - Pengfei Wang; Xinyan Liu; Yaxin Zheng; Hanting Qu; Jingpeng Li; Ruiping Wang; Yu Ji; Da Xu; Fucheng Ding; Peng Zhang; Haijing Liu; Yuying Bao (Applied Soil Ecology, 2025)

Effects of conventional and biodegradable microplastics at comparable environmental levels on pesticide degradation in soil - Pengtao Chen; Furong Fu; Lixia Zhao; Xiaojing Li; Yang Sun; Zhenyan Fu; Liping Weng (Applied Soil Ecology, 2025)

Long-term plastic film mulching promotes microplastic accumulation and alters gross nitrogen transformation in soil - Jinrui Zhang; Kai Wang; Tianxiang Hao; Jinbo Zhang; Christoph Müller; Perrine Florent; Hong Yan; Siyang Ren; Kaijing Qu; Kaige Ren; Jingjing Li; Yiting Su; et al. (Applied Soil Ecology, 2025)

Latitudinal patterns and phosphorus-driven regulation of abundant and rare fungal communities in coastal wetlands - Shaokun Wang; Jing Li; Lijuan Cui; Rumiao Wang; Wei Li; Juntao Wang (Applied Soil Ecology, 2025)

Toxicological effects of per- and polyfluoroalkyl substances (PFASs) on earthworms: Progress and prospects - Cheng Qin; Chenxi Lu; Chang Lu; Lixia Zhao; Xiaojing Li; Yang Sun; Liping Weng; Yongtao Li (Applied Soil Ecology, 2025)

Smooth vetch covering alters soil aggregate microbial metabolic limitations in citrus orchards - Meng Zhang; Yafei Shen; Tian Chen; Jing Li; Yongwei Zhou; Lixiong Zeng; Lei Lei; Jiajia Zhang; Wenfa Xiao; Ruimei Cheng (Applied Soil Ecology, 2024)

Pore-scale investigation of solute dispersion behavior in porous media under a two-phase co-flow condition - Chunwei Zhang; Kai Zhang; Jiale Mo; Zijing Li; Tetsuya Suekane; Yuncong Wang; Ming Li (Advances in Water Resources, 2024)

Characterizing NH3 emissions from a sheep feedlot and a manure composting facility in North China with the inverse dispersion technique - Chunjing Liu; Wenhua Liao; Yishuo Xu; Di Wu; Zhiling Gao; Jianzhi Xie (Agricultural and Forest Meteorology, 2023)

Radial and seasonal variation of sap flow and its response to meteorological factors in sandy Pinus sylvestris var. mongolica plantations in the Three North Shelterbelt of China - Yuqiang Tong; Jing Liu; Xu Han; Tong Zhang; Yinghao Dong; Mengge Wu; Shengjin Qin; Yawei Wei; Zhenju Chen; Yongbin Zhou (Agricultural and Forest Meteorology, 2023)

Optimization of aquaculture sustainability through ecological intensification in China - Shuang‐lin Dong; Yun‐wei Dong; Ling Cao; Johan Verreth; Yngvar Olsen; Wen‐jing Liu; Qi‐zhi Fang; Yan‐gen Zhou; Li Li; Jing‐yu Li; Yong‐tong Mu; Patrick Sorgeloos (Reviews in Aquaculture, 2022)
As the world's leading producer of farmed aquatic food products, China faces great uncertainty concerning the further sustainable development of its aquaculture industry due to high and increasing pressure from environmental and resource constraints. To realize truly sustainable development, it is imperative to establish an evaluation system that integrates social, economic, environmental and resource criteria, and optimizes aquaculture systems through a holistic approach. Here, we used analytical hierarchy processes combined with expert judgment and objective data to assess the sustainability of 10 major aquaculture production systems (APSs) in China. Based on the evaluation results, we propose the ecological intensification of aquaculture systems (ELIAS), rationally integrating anthropogenic inputs with aquaculture ecosystem services, to improve the sustainability of APSs. The holistic evaluation system and ELIAS are fundamental and critical for the future development of aquaculture in China and globally.

Cover Image, Volume 14, Issue 3 - Shuang‐lin Dong; Yun‐wei Dong; Ling Cao; Johan Verreth; Yngvar Olsen; Wen‐jing Liu; Qi‐zhi Fang; Yan‐gen Zhou; Li Li; Jing‐yu Li; Yong‐tong Mu; Patrick Sorgeloos (Reviews in Aquaculture, 2022)
The cover image is based on the Review Article Optimization of aquaculture sustainability through ecological intensification in China by Shuang‐lin Dong et al., https://doi.org/10.1111/raq.12648 image

Pelagic microalgae as suitable diets for the benthic harpacticoid copepod Tigriopus japonicus - Guizhong Wang; Jie Xu; Chaoshu Zeng; Qilong Jia; Lisheng Wu; Shaojing Li (Hydrobiologia, 2015)

Assessment of antioxidant defense system responses in the hepatopancreas of the freshwater crab Sinopotamon henanense exposed to lead - Na Liu; Lan Wang; Bo Yan; Yongquan Li; Fei Ye; Jing Li; Qian Wang (Hydrobiologia, 2014)